Comparison of Antioxidant Activity of Cream Preparations Combining Avocado and Green Tea Extracts Using DPPH, FRAP, and ABTS Methods - Juwita, Arti (Sciences of Phytochemistry, 2026)
The accumulation of free radicals causes oxidative stress, which contributes to premature aging, collagen tissue damage, and hyperpigmentation. One preventive measure is the use of antioxidants in cosmetic products, particularly skin-lightening creams. Natural ingredients such as avocado (Persea americana) and green tea (Camellia sinensis) are known to be rich in bioactive compounds, including vitamin E, flavonoids, and polyphenols (EGCG), which possess high antioxidant potential and are safe for use. This study aims to compare the antioxidant activity of a combination cream formulation of avocado fruit extract (EDA) and green tea leaf extract (EDT) using three testing methods: DPPH, FRAP, and ABTS. The extracts were obtained through supercritical fluid extraction (avocado) and ethanol maceration (green tea), then formulated into various cream concentrations. The DPPH test results showed that formula F2 had the best radical scavenging ability with an IC₅₀ value of 336.34 µg/mL. The FRAP test showed a clear dose-response relationship, with formula F4 achieving the highest reduction capacity of 522.08 mMol Fe²⁺/g. The ABTS test also confirmed this trend, with F4 exhibiting the highest activity (599.64 mM TE/g), more than 200 times higher than the negative control. These findings demonstrate a synergistic effect between EDA and EDT, making their combination highly promising as active ingredients in antioxidant-based skin-lightening cosmetics.